Determination of some environmental factors on milk yield traits and milk components in Simmental cows - Sahin, Onur; Soysal, Mehmet Ihsan; Gurcan, Eser Kemal (Tubitak Scientific & Technological Research Council Turkey, 2024)
The aim of the study was to determine the effects of various environmental factors on milk yield and milk components in Simmental cows. In the present study, 33,813 milk yield records from 1631 cows and milk samples from 233 cows were used for milk component analysis. Lactation milk yield (LMY) and 305 -day yield (305-DMY) were the milk yield characteristics studied. Environmental factors considered for milk yield characteristics included province, calving year, calving month, parity, age, and lactation length. Milk components analyzed were fat percentage (FP), protein percentage (PP), lactose percentage (LP), somatic cell count (Log(10)SCC), and dry matter (DM). Environmental factors considered for milk components were province, birth year, control month, calving month, and parity. The results indicated that all environmental factors significantly influenced milk yield characteristics (p < 0.01). Specifically, province and birth year significantly affected FP and Log(10)SCC (p < 0.01), whereas calving month, control month, and parity did not significantly affect FP. Province, birth year, and control month significantly influenced PP and DM (p < 0.01), while calving month and parity did not significantly affect PP. Province was the only significant factor for LP (p < 0.01). Considering all data, the averages of traits were as follows: LMY (5628.1 +/- 12.80 kg), 305-DMY (5309.2 +/- 11.80 kg), total dry matter yield (TDMY) (22.58 +/- 0.51 kg), DM (12.43 +/- 0.08%), Log10SCC (2.29 +/- 0.04, equivalent to 226239 cells/mL), FP (3.78 +/- 0.06%), PP (3.57 +/- 0.02%), and LP (4.72 +/- 0.01%).
Keywords: Simmental; milk component; milk yield; environmental factors